Cocais, a cidade reinventada . Cocais, the Reinvented Town - Cardoso, Ines (Plateau Produções, 2008)
Verzio FF Submission An untraditional view of a community of inmates at a dilapidated psychiatric clinic in the remote village of Cocais, Sao Paolo. The director follows the inmates as they prepare for a wild masked wedding ball and feast. The ball is attended by residents of the village and their children, and in the revelry it is not at all clear who is in the institution involuntarily. A 'wall' is temporarily demolished and the difference between sanity and insanity becomes irrelevant.